2015
DOI: 10.1177/1524500415582070
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Effect of the Mere Presence of a Religious Symbol on Compliance With an Organ Donation Request

Abstract: Identifying low-cost, effective methods to influence behavior is of keen interest to social marketers and others striving to bring about social change. Research on material primes (an object or a word present in the individual’s environment) has received little interest from scientists. This field study conducted in France examined whether the presence of a religious symbol could influence the number of individuals who accepted an organ donation card. The study, conducted with 200 males and 200 females, examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…In relation to bystander intervention, several researchers have found religious beliefs to be positively correlated with pro‐social helping behavior and the desire for people to be treated fairly (Begue, ; Park & Smith, ). For example, Gueguen, Bougeard‐Delfosse and Jacob () demonstrated how religious symbols could encourage people to sign up to donate organs simply from the symbolism of a person wearing or not wearing a cross when asking for participation. In an advertisement, using the word “Christian,” Henley et al () were able to garner more favorable attitudes and purchase intentions, than when the Christian word was not present.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In relation to bystander intervention, several researchers have found religious beliefs to be positively correlated with pro‐social helping behavior and the desire for people to be treated fairly (Begue, ; Park & Smith, ). For example, Gueguen, Bougeard‐Delfosse and Jacob () demonstrated how religious symbols could encourage people to sign up to donate organs simply from the symbolism of a person wearing or not wearing a cross when asking for participation. In an advertisement, using the word “Christian,” Henley et al () were able to garner more favorable attitudes and purchase intentions, than when the Christian word was not present.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to symbolic interactionism (Blumer ), symbols help define one's reality and are learned and shared through social interactions. As an example, Guéguen, Bougeard‐Delfosse, and Jacob () found that the mere presence or absence of a cross on a volunteer asking people to consider organ donation led to a statistically significant increase in agreement when the cross was worn. Similarly, a relevant (vs. irrelevant) connection between the word ‘‘Christian” and a product (e.g., book store vs. beer) can lead to favorable ad attitudes and purchase intentions (Henley et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…All religious leaders propagate positive attitude towards donating organs (Skowronski, ), and also, religious symbols have a positive impact on the formation of ODA (Guéguen, Bougeard‐Delfosse, & Jacob, ). Majority of world religions (Ryckman, van den Borne, Thornton, & Gold, ) and religious leaders (Gallagher, ) support OD.…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%